The Stability of Islamic Finance : Creating a Resilient Financial Environment for a Secure Future. - Iqbal, Zamir (John Wiley & Sons, 2011)
The Stability of Islamic Finance main focus is on the question of the sources of financial instability which seems inherent in the conventional system. As a core component of this focus, the book will consider episodes of turbulence and instability in a historical context recalling the occurrence of such events from mid-19th century to the present. It will present various theoretical explanations along with solutions and alternative financial systems that avoid instability provided by various scholars dating back to mid-19th century to present. The book then will present and discuss the archit.